Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1080/02522667.1991.10699058
|View full text |Cite
|
Sign up to set email alerts
|

Ratio and Product Type Exponential Estimators

Abstract: This paper proposes new ratio and product type estimators for estimating the mean of the finite population using information on single auxiliary variable. The bias and mean square error of these estimators have been obtained. These estimators are compared fer their precision with usual mean per unit, ratio and product estimators and are found to be more efficient in many practical situations. Further, it is shown that these estimators reduce to regression estimator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
223
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(250 citation statements)
references
References 2 publications
0
223
0
Order By: Relevance
“…It is shown that proposed exponential type estimator is always more efficient than estimators considered by Bahl and Tuteja (1991) and Singh, Chauhan, Sawan, and Smarandache (2009). From numerical examples it is also observed that proposed modified ratio estimator performs better than existing estimators.…”
mentioning
confidence: 82%
“…It is shown that proposed exponential type estimator is always more efficient than estimators considered by Bahl and Tuteja (1991) and Singh, Chauhan, Sawan, and Smarandache (2009). From numerical examples it is also observed that proposed modified ratio estimator performs better than existing estimators.…”
mentioning
confidence: 82%
“…Motivated by Bahl and Tuteja (1991) the imputation techniques utilizing the exponential-type estimator are defined as: …”
Section: Exponential Methods Of Imputationmentioning
confidence: 99%
“…Thus, we compare the product type estimators with each other. Finally, we compare the MSE of our new product type exponential estimators with the MSE of the classical product estimator, the product type exponential estimator given by Bahl and Tuteja [1] and our new product estimators. We obtain…”
Section: Efficiency Comparisons Of Estimatorsmentioning
confidence: 99%